Efektivitas Media Video Tutorial terhadap Keterampilan Membuat Lip Balm bagi Tunarungu - Rini Elvida; Ardisal Ardisal (Universitas Negeri Padang, 2018)
This study aims to evaluate the effectiveness of video tutorials to improve the skills in making lip balm for deaf people. This research used experiment approach with one-group pretest posttest design. The sample of this research are five deaf people in Gerkatin Padang. The skills examined by pretest and posttest are proccessed and compared by using Wilcoxon Sign Rank Test. Based on the result of pretest and posttest it is known that the mean score of pretest is 19,80 and the mean score of posttest is 30.20. The mean scores would later processed to find the differences with using Wilcoxon Sign Rank Test. From the result of data analysis, it is found 2,032 and Asymp Sig (2-tailed) = 0,042 in significant degree 95% and α=0,05. The alternative hypothesis is accepted because t > Asymp Sig (2-tailed). Therefore, it is concluded that video tutorial is effective in improving the skills of making lip balm for deaf people in Gerkatin Padang. This research suggests for deaf people loss in Gerkatin Padang to use video tutorial to improve the skills in making lip balm for others.